VARIABEL YANG MEMPENGARUHI KEPUASAN KERJA DAN TURNOVER INTENTION PEGAWAI DINAS PENDIDIKAN KABUPATEN PROBOLINGGO - Afrianti, Nurohma; Titisari, Purnamie; Handriyono, Handriyono (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2018)
This study aims to examine the effect of work stress, organizational climate, and employee engagement on work satisfaction and turnover intention of the staffs of Education Department of Probolinggo Regency. The research sample consists of 83 respondents. Data were analyzed using path analysis. Results of the research show that work stress, organizational climate, and employee engagement have direct effect and indirect effect through work satisfaction on turnover intention of the staffs of Education Department of Probolinggo Regency. Keywords: Work Stress, Organizational Climate, Employee Engagement, Work Satisfaction, and Turnover Intention.